2010
DOI: 10.1113/jphysiol.2009.186262
|View full text |Cite
|
Sign up to set email alerts
|

Glycine transporter GLYT1 is essential for glycine-mediated protection of human intestinal epithelial cells against oxidative damage

Abstract: Glycine protects mammalian intestine against oxidative damage caused by ischaemiareperfusion (IR) injury and prevents or reverses experimentally-induced colitis. However the mechanism of protection remains largely unknown. The objectives of the current study were to demonstrate directly glycine-mediated protection of human intestinal epithelial cells and to determine the requirement for glycine uptake by the specific transporter GLYT1. Exogenous glycine protected human intestinal Caco-2 and HCT-8 cells against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 62 publications
1
40
0
2
Order By: Relevance
“…Alternatively, the combined effects of PKG-I and PKA on GLYT1 activity may result in activation instead of inhibition of the transport. The rise in GLYT1 transport by NO may explain the finding that GLYT1 activity has been reported as essential for glycine-mediated protection of human intestinal epithelial cells against oxidative damage (74). This issue deserves future research.…”
Section: Discussionmentioning
confidence: 93%
“…Alternatively, the combined effects of PKG-I and PKA on GLYT1 activity may result in activation instead of inhibition of the transport. The rise in GLYT1 transport by NO may explain the finding that GLYT1 activity has been reported as essential for glycine-mediated protection of human intestinal epithelial cells against oxidative damage (74). This issue deserves future research.…”
Section: Discussionmentioning
confidence: 93%
“…Measurements made using a GLYT2 specific inhibitor, ALX-1393, confirmed molecular data indicating the absence of this transporter in human intestinal cells. 15) 2.2. Function That GLYT1 activity predominates at the basolateral membrane leads to questions about its function.…”
Section: Introductionmentioning
confidence: 99%
“…In both enterocytes and colonocytes, GLYT1 is restricted to the plasma membrane and located at both apical and basolateral surfaces. 14,15) While it has not been possible to determine by functional or immunological methods the GLYT1 isoform/s present in intestine, as suitable antibodies and selective inhibitors 12) remain elusive, studies at the molecular level have shown that the predominant transcript variant is that which encodes GLYT1A. 16) Although several other GLYT1 transcript variants were detectable in human intestine by polymerase chain reaction (PCR), including those for GLYT1B and GLYT1C and a number which were previously undescribed, these were all found at very low concentration and detection was inconsistent, suggesting again that some if not all arose as unstable intermediates or errors of the splicing process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations